2013
DOI: 10.1007/s10689-013-9622-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel and recurrent BRCA1/BRCA2 mutations in early onset and familial breast and ovarian cancer detected in the Program of Genetic Counseling in Cancer of Valencian Community (eastern Spain). Relationship of family phenotypes with mutation prevalence

Abstract: During the first 6 years of the Program of Genetic Counselling in Cancer of Valencia (eastern Spain), 310 mutations (155 in BRCA1 and 155 in BRCA2) in 1,763 hereditary breast (BC) and ovarian cancer (OC) families were identified. Of the mutations found 105 were distinct (53 in BRCA1 and 52 in BRCA2), eight new and 37 recurrent. Two of the novel mutations were frame-shift placed in exons 2 and 11 of BRCA1 and the remaining six were placed in BRCA2; four frame-shift (three in exon 11 and one in exon 23), one del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…These founder mutations have also been reported in Spain [2830]. Therefore, these Ashkenazi Jew mutations are thought to come from areas of Spain where Jews communities settled during the early Common Era.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…These founder mutations have also been reported in Spain [2830]. Therefore, these Ashkenazi Jew mutations are thought to come from areas of Spain where Jews communities settled during the early Common Era.…”
Section: Introductionmentioning
confidence: 80%
“…For example, women from Argentina, Mexico, and Brazil have a higher prevalence of BRCA1 mutations [13, 18, 27], whereas in women from the Caribbean (Cuba and Puerto Rico), BRCA2 is more frequently mutated [24, 25]. Studies of women with BC from Spain showed a larger number of rearrangements in both BRCA genes when compared to Hispanic women [2830]. Additionally, several mutations for both BRCA genes were found in Hispanic subpopulations, especially in Argentina where there is a higher proportion European admixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three BRCA2 recurrent mutations were identified (c.2808_2811delACAA, c.3264dupT and c.9026_9030delATCAT), representing 21.3 % of the total mutations (Table 4). These recurrent mutations have also been found in ICs and most of them have already been reported in studies carried out in Spanish population [26][27][28][29][34][35][36][37][38] or included in mutation databases [30,31] (Table 4). …”
Section: Discussionmentioning
confidence: 92%
“…Sixteen mutations detected in ICs, one in BRCA1 and 15 in BRCA2, previously reported in the Spanish population [26][27][28][29]38] (Table 2). In addition, prevalent BRCA2 mutations have been reported in previous Spanish population studies.…”
Section: Discussionmentioning
confidence: 99%